Role of vaginal mucosa, host immunity and microbiota in vulvovaginal candidiasis - Balakrishnan, Subatrra Nair; Yamang, Haizat; Lorenz, Michael C.; Chew, Shu Yih; Than, Leslie Thian Lung (MDPI, 2022)
Vulvovaginal candidiasis (VVC) is a prevalent gynaecological disease characterised by vaginal wall inflammation that is caused by Candida species. VVC impacts almost three-quarters of all women throughout their reproductive years. As the vaginal mucosa is the first point of contact with microbes, vaginal epithelial cells are the first line of defence against opportunistic Candida infection by providing a physical barrier and mounting immunological responses. The mechanisms of defence against this infection are displayed through the rapid shedding of epithelial cells, the presence of pattern recognition receptors, and the release of inflammatory cytokines. The bacterial microbiota within the mucosal layer presents another form of defence mechanism within the vagina through acidic pH regulation, the release of antifungal peptides and physiological control against dysbiosis. The significant role of the microbiota in maintaining vaginal health promotes its application as one of the potential treatment modalities against VVC with the hope of alleviating the burden of VVC, especially the recurrent disease. This review discusses and summarises current progress in understanding the role of vaginal mucosa and host immunity upon infection, together with the function of vaginal microbiota in VVC.